A Reconstrução do Conhecimento do Professor de Inglês: Questionando as Ações Rotineiras - Castro, Solange T. Ricardo de (The ESPecialist, 2012)
This study discusses the process of reconstruction of knowledge of two teachers of English by focussing on the researcher’s questioning of the teachers’ everyday instructional actions. It is part of a broader on-going research on teacher development. First, the context of the study is presented. Next, as the main theoretical underpinnings of the work, the roles of language as the mediator in processes of acquisition of knowledge are discussed: (a) language as a tool for reflection or for reproduction of unquestioned meanings, and (b) language as the very locus where meanings are built or (trans)formed. Thirdly, the methodological procedures are presented. Finally, the effects of the researcher’s interventions in the process of constitution of the teachers' knowledge are discussed, illustrated by examples taken from the on-going research.